Innovative Online eBusiness Model: Digital Business - Sultana, Mahreen (IJRDO - Journal of Business Management, 2018)
The proliferation of new technologies and their implications for the future business will be flourish the way for entrepreneur in online business by the utilization of innovation idea . Globally, online business is projected to be nearly $500 billion by 2018 .With easy accessibility of internet and intensified consumer expectations for different needs and wants embolden entrepreneurs to present their idea in distinctive way as per the needs and wants of target customers.Globally, algorithm-driven delivery models and analytics enable urban customers to get products delivered faster, more flexibly, and sometimes less expensively than in the past. Generation of innovative ideas and competition in the existing market are the major elements for an entrepreneur to run in long run by providing excellent customer service.To signify the business more efficiently towards the potential customers the idea must be valid and up to the market expectation both in long run and short run (as a way of pilot study). The theme of the paper is, “Innovative Online Business Model”  which represents, three online business model for three different countries based on their business opportunities and growths in that chosen particular business. The paper is divided into three main sections where each section analyse online business model, Core Value Proposition, the Sources and Methods of Revenue Generation, and the potential for growth. Finally, the paper recommend how might incorporate these technologies and related strategies into its business going forward.